Comparative plasma and urine metabolomics analysis of juvenile and adult canines - Wu, Taibo; Chen, Yun; Yang, Mingzi; Wang, Shuang; Wang, Xiaoming; Hu, Manli; Cheng, Xu; Wan, Juan; Hu, Yufeng; Ding, Yi; Zhang, Xin; Ding, Mingxing; et al. (Frontiers in Veterinary Science, 2023)
Physiological growth and aging are closely correlated with the metabolite profile that determines health and homeostasis. Thus, UHPLC-Q-TOFMS-based metabolomics investigations of canines biofluids can provide detailed information about the changes in biological processes and multiple metabolic profiles associated with aging. The blood and urine samples were collected from 15 young and 15 adult beagle dogs, and blood routine analysis and serum biochemical analysis were initially performed to compare physiological status between young and adult animals. In addition, serum and urine samples were used for non-targeted metabolomics analysis. We detected that the white blood cell count and platelet count gradually decreased with development, whereas the liver function indexes in the young group were much lower than that in the adult ones. The metabolomics analysis results showed the age significantly changed the plasma and urine metabolism which was characterized by the declined levels of metabolism from particular alanine, aspartate and glutamate metabolism, arginine biosynthesis, bile secretion, and histidine metabolism. For urine metabolomics, the most obvious age-related pathways include bile secretion and cysteine and methionine metabolism. Importantly, we clearly showed that the levels of glutamine, methylmalonic acid, and L-carnitine were consistently higher in both serum and urine of adults, while N-acetylhistamine, uracil, and cytidine 5’-triphosphate concentrations were much lower in the adult group compared to younger ones. Our study provides a whole profile of serum and urine characteristics of young and adult canines, identifying significant changes in several plasma and urine metabolites involved in amino acid metabolism and bile secretion, which supports the development of preventive and therapeutic strategies for age-related physiological homeostasis.